Understanding the Effects of Coronavirus on Australian Households: A Macro–Micro Analysis. Issue 3 (30th June 2022) - Mariano, Marc Jim; Verikios, George
Abstract : The coronavirus (COVID‐19) pandemic brought economic recession that affected nations, businesses, and households globally. The severity of this global economic crisis is large and the impact has been asymmetric across socioeconomic groups. We examine the distributional effects of the COVID‐19 pandemic across household types using a specially‐designed model that combines macro (computable general equilibrium) and micro (heterogenous households) approaches. Computable general equilibrium models are able to capture behavioural changes in macroeconomic and sectoral variables but they often lack the rich distributional detail found in microsimulation models. In this paper, we address this limitation by incorporating 10, 046 actual households into a computable general equilibrium model to capture the heterogeneity through which the pandemic may influence household behaviour. We find that the income effects are asymmetric across income groups leading to a slight increase in income inequality. The distributional effects are more progressive for non‐wage income sources and uniform for wage income. For younger cohorts, income changes are dominated by employment effects whereas income changes for older cohorts are dominated by changes in capital rentals and government transfers. Spatially, the income effects follow a similar pattern for city and non‐city dwellers.